2008
DOI: 10.1038/oby.2008.337
|View full text |Cite
|
Sign up to set email alerts
|

β‐Aminoisobutyric Acid Prevents Diet‐induced Obesity in Mice With Partial Leptin Deficiency

Abstract: β-Aminoisobutyric acid (BAIBA), a thymine catabolite, increases fatty acid oxidation (FAO) in liver and reduces the gain of body fat mass in Swiss (lean) mice fed a standard chow. We determined whether BAIBA could prevent obesity and related metabolic disorders in different murine models. To this end, BAIBA (100 or 500 mg/kg/day) was administered for 4 months in mice totally deficient in leptin (ob/ob). BAIBA (100 mg/kg/day) was also given for 4 months in wild-type (+/+) mice and mice partially deficient in le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
115
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(126 citation statements)
references
References 60 publications
11
115
0
Order By: Relevance
“…Plasma ALT was higher in obese mice compared with their lean counterparts (Fig. 1A), reflecting liver damage as reported previously (Robin et al, 2005;Begriche et al, 2008b). However, ethanol administration did not change ALT values in both groups of mice (Fig.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Plasma ALT was higher in obese mice compared with their lean counterparts (Fig. 1A), reflecting liver damage as reported previously (Robin et al, 2005;Begriche et al, 2008b). However, ethanol administration did not change ALT values in both groups of mice (Fig.…”
Section: Resultssupporting
confidence: 62%
“…Indeed, phosphorylation of ACC leads to the inactivation of its activity, reducing hepatic levels of malonyl-CoA, the only endogenous inhibitor of CPT-1 (Begriche et al, 2008b(Begriche et al, , 2009. In this study, hepatic phospho-ACC was significantly augmented in ethanol-treated ob/ob mice, and this was associ- .…”
supporting
confidence: 53%
See 1 more Smart Citation
“…One of the major advantages of these genetic murine models of obesity is the rapid and consistent occurrence of insulin resistance, hyperglycemia, and NAFLD (Lindström, 2007;Trak-Smayra et al, 2011;Massart et al, 2012), whereas high-fat diet-induced obesity is not always associated with these secondary metabolic disorders, even after several months of feeding (Burcelin et al, 2002;Begriche et al, 2008a). It is noteworthy that both ob/ob and db/db mice are characterized by "borderline NASH," because fatty liver is associated with moderate hepatic necroinflammation and mild fibrosis Begriche et al, 2008b;Trak-Smayra et al, 2011). Moreover, this study and previous investigations (Trak-Smayra et al, 2011) showed comparable basal levels of plasma transaminases between ob/ob and db/db mice, indicating a similar degree of hepatic cytolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Begriche et al demonstrated that β-aminoisobutyric acid (BAIBA), a natural catabolite of thymine, reduced body fat percentage through increased fatty acid oxidation and decreased de novo lipogenesis in mice [2]. Recently, Roberts et al identified BAIBA as a small molecule myokine secreted from myocytes with forced expression of peroxisome proliferator-activated receptor-gamma coactivator-1α (PGC-1α).…”
Section: Introductionmentioning
confidence: 99%